“Playing jazz is what she does”: The impact of peer identification and mastery experiences on female jazz pupils’ self-efficacy at Improbasen - Johansen, Guro Gravem (Frontiers in Education, 2023)
This article is a conceptual analysis of the concepts of enactive mastery experience and vicarious learning experience from Albert Bandura’s socio-cognitive theory, applied to the empirical case of the Norwegian learning centre Improbasen. I outline some historical and socio-psychological contexts that posits jazz practice as a masculine stereotyped activity, to indicate various mechanisms that may cause a low self-efficacy for playing jazz in girls and non-binary children. When presenting the empirical case, I highlight the learning centre’s strategies to promote gender equality. Finally, I discuss theoretically how these strategies may strengthen self-efficacy in children, relating them to experiences of mastery and vicarious learning. In conclusion I suggest that a diverse learning environment that facilitates peer identification works better for all genders than when iconic male jazz musicians are treated as models for learning.